Pembelajaran Berbasis Teknologi Informasi dan Komunikasi Pada Mata Pelajaran Bahasa Inggris dan Matematika - Andi Dian Rahmawan; Nendra Mursetya Somasih Dwipa (ABDIMAS DEWANTARA, 2019)
Both Math and English are the two subjects that most of students have difficulty on it. To understand Math requires logical thinking that most of students do not have. To understand English, in which the written and sound are different with our first language, requires habit to hear and write English a lot. Students need to be accustomed to using English on everyday activities. In fact, most of students tend to use Javanese or Indonesian to communicate to others. Teachers also get difficulties on motivating students to learn Math and English for the better future. Some students have struggled to learn them, but still, the results are not satisfying.Observing this phenomenon, as the lecturers of English and Math, we are trying to help the teachers on giving material with the different point of views. We introduced different approaches on giving exposure to students about Math and English. English will be taught by employing Podcast, math will be introduced by using Geogebra. It is expected that teachers and students will have another perspectives; we can say that the teachers may have another style of teaching and students will get additional learning styles.